Noninvasive ventilation for acute exacerbations of asthma: A systematic review of the literature. Issue 6 (November 2017) - Green, Elyce; Jain, Paras; Bernoth, Maree
Abstract: Background: Asthma is a chronic disease characterised by reversible airway obstruction caused by bronchospasm, mucous and oedema. People with asthma commonly experience acute exacerbations of their disease requiring hospitalisation and subsequent utilisation of economic and healthcare resources. Noninvasive ventilation has been suggested as a treatment for acute exacerbations of asthma due to its ability to provide airway stenting, optimal oxygen delivery and decreased work of breathing. Objectives: This paper is a systematic review of the available published research focused on the use of noninvasive ventilation for the treatment of acute exacerbations of asthma to determine if this treatment provides better outcomes for patients compared to standard medical therapy. Method: Database searches were conducted using EBSCOhost, MEDLINE and PubMed. Search terms used were combinations of 'noninvasive ventilation', 'BiPAP', 'CPAP', 'wheez*' and 'asthma'. Articles were included if they were research papers focused on adult patients with asthma and a treatment of noninvasive ventilation, and were published in full text in English. Included articles were reviewed using the National Health and Medical Research Council (Australia) evidence hierarchy and quality appraisal tools. Results: There were 492 articles identified from the database searches. After application of inclusion/exclusion criteria 13 articles were included in the systematic review. Studies varied significantly in design, endpoints and outcomes. There was a trend in better outcomes for patients with acute asthma who were treated with noninvasive ventilation compared to standard medical therapy, however, the variability of the studies meant that no conclusive recommendations could be made. Conclusion: More research is required before noninvasive ventilation can be conclusively recommended for the treatment of acute exacerbations of asthma.